2007
DOI: 10.1002/ldr.818
|View full text |Cite
|
Sign up to set email alerts
|

Extent and characterisation of salt‐affected soils in Iran and strategies for their amelioration and management

Abstract: Salinisation of land resources is a major impediment to their optimal utilisation in many arid and semi-arid regions of the world including Iran. Estimates suggest that about 34 million ha, including 4Á1 million ha of the irrigated land, are salt-affected in Iran as the consequence of naturally occurring phenomena and anthropogenic activities. The annual economic losses due to salinisation in the country are more than US$ 1 billion. With variable levels of success, different approaches-salt leaching and draina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 20 publications
1
70
0
Order By: Relevance
“…In fact, organic manures result a greater adsorption of Ca 2+ , Mg 2+ and K + than Na + which leads to lower soil ESP (Murtaza et al, 2009). Moreover, Qadir et al (2008) and Walker and Bernal (2008) reported that an acceleration of Na + leaching considerably decreases the ESP and EC.…”
Section: Tuber Yield Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, organic manures result a greater adsorption of Ca 2+ , Mg 2+ and K + than Na + which leads to lower soil ESP (Murtaza et al, 2009). Moreover, Qadir et al (2008) and Walker and Bernal (2008) reported that an acceleration of Na + leaching considerably decreases the ESP and EC.…”
Section: Tuber Yield Parametersmentioning
confidence: 99%
“…In addition, by supplying major nutrients particularly N, P and K, the biofertilizers improve the mineral nutrient status and growth of plants grown in salt-affected soils (Qadir et al, 2008). In the same sense, organic matter can improve the microbiological activity of soil that plays a pivotal role in carbon mineralization and nutrient cycling.…”
Section: Introductionmentioning
confidence: 99%
“…According to a soil database containing information from 10 Iranian provinces covering the most important agricultural areas, the concentration of K in soil is the highest among macronutrients (Jalali, 2015). The salinisation of land resources in Iran is the consequence of both natural phenomena (geological composition of parent material, stream salinity, wind-borne salinity, seawater intrusion, low rainfall and high evaporation) and anthropogenic activities (irrigation with saline/sodic surface or ground water, inadequate irrigation management practices and drainage facilities, over-grazing of pastures/vegetation) (Qadir et al, 2008). The present study investigated the impact of K and Na (with a focus on K) on soil structure, its stability and associated properties, and functions, using a loamy soil from north-eastern Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Ambiental, v.17, n.9, p.1005-1013, 2013. seen in Planosols (CHESF, 1987;Silva et al, 2007). The pH is neutral to moderately alkaline ( Figure 5A) (EMBRAPA, 2006) as a result of the exchangeable sodium percentage (Qadir et al, 2008) and also of carbonate content, with values from 5 to 16% (CHESF, 1987). Due to the above characteristics these soils may have a nutrient imbalance or deficiency, particularly of iron and manganese (Sanchez et al, 2003;Qadir et al, 2006).…”
Section: (D) Cation Exchange Capacity (Cec) (E) Electrical Conductivmentioning
confidence: 99%